Can ultrasound be an assessment tool for sagittal spine mobility and chest expansion in patients with ankylosing spondylitis?. Issue 39 (September 2018) - Yurdakul, Ozan Volkan; Rezvani, Aylin
Abstract : Abstract: We aimed to examine whether ultrasound (US) is useful for evaluating spinal mobility and chest expansion in ankylosing spondylitis (AS) patients and determine a cutoff value to identify reduced sagittal lumbar mobility. Our cross-sectional study included 50 AS patients and 50 controls. Metric measurements and Bath AS indices were measured in AS patients. The distance between C6-C7, T11-T12, and L4-L5 vertebrae was measured, and the difference and percentage of difference between erect position and maximal cervical and lumbar flexion was calculated (T11-T12dif, T11-T12%, L4-L5dif, L4-L5%, T+Ldif, T+L%). Intercostal divergence was measured 1.5 cm away on the left from the sternocostal space during maximum inhalation and maximum exhalation, and the difference and percentage of difference between them was calculated (ICdif, IC%). All metric measurements were lower in the AS group except for tragus-to-wall distance. T11-T12dif, T11-T12%, L4-L5dif, T+Ldif, and T+L% values were higher in the control group, while other US measurements did not differ between the groups. All US measurements except ICdif and IC% correlated with the Bath AS Metrology Index. Thus, US may be used for assessing spinal mobility in patients with AS. T11-T12dif <0.79 cm may show decreased lumbar sagittal mobility.